Enabling social exploration through virtual guidance in google expeditions: An exploratory study - Parmaxi, Antigoni; Stylianou, Kostas; Zaphiris, Panayiotis (My University, 2018)
This paper reports on an exploratory study on the use of Google Expeditions in the context of an intensive 650-h Greek language course for specific academic purposes. Google Expeditions are collections of linked virtual reality (VR) content and supporting materials that can enable teachers to guide students through virtual trips to places throughout the world including museums, surgical processes, outer space, the ocean etc. Qualitative thematic analysis of instructors’ field notes, students’ reflections, interviews and focus group was employed aiming at identifying the potential of Google Expeditions as instructional tools that can extend the language course for specific academic purposes in topics related to Nursing. To triangulate the findings, the study also collected data by observing students’ behavior in the use of Google Expeditions. The use of Google Expeditions enabled students to extend the borders of the classroom by making virtual walkthroughs in places that would normally be unreachable and trigger social exploration through inter- and extra-VR communication, sharing of ideas, concepts, experiences and artifacts. The outcomes have shown that actions taken by the students and instructor during a virtual trip in nursing-related places reveal results in favor of the use of Google Expeditions in the language classroom. Further implications for practitioners and researchers are also provided.
Keywords: Constructionism; Google expeditions; Low-cost vr; Social constructionism; Technology-Enhanced learning; Virtual reality; VR; Wearable